An analytical approach of the chromaticity correction for compact hadron river. Issue 1 (March 2021) - Wah, Leo Kwee; Takayama, Ken; Adachi, Toshikazu; Kawakubo, Tadamichi; Dixit, Tanuja
Abstract: A design of a compact hadron driver for future cancer therapies based on the induction synchrotron concept is given. In order to realize a slow extraction technique in a fast cycling synchrotron, which allows the energy sweep beam scanning, the zero momentum-dispersion D(s) region and high flat D(s) region are necessary. The present design lattice which meets both requirements. In this study, details of the lattice parameters is introduced and an analytical solution for chromaticity correction are described and discussed.